In their own words: a qualitative exploration of Agnew’s storylines among imprisoned offenders - Howerton-Orcutt, Amanda (Journal of Theoretical and Philosophical Criminology, 2020)
Agnew (2006) developed the concept of “storylines,” which are a category of variables that temporally exist between stable background factors (i.e. low self-control) and temporary situational factors (i.e. the absence of capable guardians). Storylines begin with some event that is out of the ordinary that temporarily alters the individual’s background factors, individual interactions with others, and/or settings encountered by an individual in ways that increase the likelihood of crime. Using data collected from thirty-five in-depth interviews with British convicts, this study will examine the presence of the five major storylines conducive to crime developed by Agnew (2006). Additionally, evidence of a sixth storyline will also be discussed followed by policy and practice implications of these findings.